The visual vernacular: the canonization and celebration of the Uganda martyrs as a mark of post-conciliar change in the Catholic Church - Erickson, K (2019)
The Uganda Martyrs have grown to become one of the country’s most persistent national symbols throughout the last 130 years. They maintain a commanding presence in everyday life to this day, both as a symbol of the Christian faith and of Ugandan perseverance and character amidst hardship. This thesis seeks to examine the legacy of these martyrs as they took on an increasingly pivotal role in public discourse in the early years of Ugandan independence, as promoted and transmitted by the Roman Catholic Church (RCC). Specifically, it tracks the lively and enthusiastic co-opting of the Martyrs’ story into the workings of the Second Vatican Council, and in the RCC’s concentrated post-Conciliar activity in the developing world in two critical moments: the canonization of the Martyrs during a session of the Council in 1964, and Paul VI’s subsequent visit to Uganda to bless the new shrines to the martyrs being built there in 1969. Both of these events provided ideal outlets for the RCC to display a new approach to Christianity in the developing world based on the liturgical reforms of the Second Vatican Council, which had concluded in 1965. This thesis utilises a novel combination of visual and written source material, bringing together work on the Second Vatican Council, Ugandan postcolonialism, and modernist architectural theory. It seeks to combine written material, in the form of official RCC documents and European press coverage, with a variety of visual media. It relies on extended fieldwork and site visits conducted in the greater Kampala area in addition to European archival material. Ultimately, the story of the Uganda Martyrs provides a unique insight into the interaction point between the global RCC and the local Ugandan Christian community.